A Sr-Nd-Hf isotope characterization of dust source areas in Victoria Land and the McMurdo Sound sector of Antarctica. (1st June 2016) - Blakowski, Molly A.; Aciego, Sarah M.; Delmonte, Barbara; Baroni, Carlo; Salvatore, Maria Cristina; Sims, Kenneth W.W.
Abstract: Determining the geographical provenance of dust provides crucial insight into the global dust cycle. For the East Antarctic Ice Sheet (EAIS), the importance of Southern hemisphere potential dust sources has been thoroughly investigated using radiogenic isotopes, whereas proximal dust source areas located on the periphery of the ice sheet remain poorly documented from a geochemical standpoint. In this work, we expand the existing isotopic (SrNd) catalogue of dust and sand-sized sediments from Victoria Land and the McMurdo Sound sector, and incorporate Hf isotopic data to place additional constraints on dust source identification. The isotopic field for materials considered in this study is characterized by 87 Sr/ 86 Sr ratios ranging from 0.703 to 0.783, εNd between −12.01 and 6.36, and εHf from −16.77 to 6.89. As reported in previous works, the data reveal close relationships between Antarctic sediments and distinct parent lithologies; in addition, our findings emphasize the background presence of very fine dusts originating from dominant global sources and regional volcanic activity as barriers to direct source-to-sink comparison of isotopic signatures. Thus, geochemical characterizations of dust sources to the Antarctic ice sheet involving multiple size fractions, including coarser-grained particles more susceptible to short-range transport, can help us to rule out global sources of dust when examining local sediment cores and ice cores. Highlights: The Sr-Nd-Hf isotopic catalogue of Antarctic PSAs is crucially expanded. Background aerosols complicate the source-to-sink comparison of isotopic signatures. Radiogenic Hf isotopes may be helpful for ruling out remote dust sources.